Effects of Increasing Hydrocortisone to 300 mg Per Day in the Treatment of Septic Shock: a Pilot Study. Issue 5 (November 2016) - Hyvernat, Hervé; Barel, Rémy; Gentilhomme, Anne; Césari-Giordani, Jean François; Freche, Annie; Kaidomar, Michel; Goubaux, Bernard; Pradier, Christian; Dellamonica, Jean; Bernardin, Gilles
ABSTRACT: Purpose: The Surviving Sepsis Campaign guidelines recommend hydrocortisone in septic shock only when fluid resuscitation and vasopressors fail to restore hemodynamic stability. Hydrocortisone administration modalities are supported only by low-grade recommendations. Our main objective here was to determine differences in 28-day mortality between two low-dose hydrocortisone regimens for the treatment of septic shock. Methods: We performed a multicenter, prospective, randomized, double-blind, pilot study in four adult medical intensive care units. Patients presenting septic shock were rapidly administered one of two regimens of hydrocortisone, either a 50-mg intravenous bolus every 6 h during 7 days (200-mg group; n = 59) or a 100-mg initial bolus followed by a continuous infusion of 300 mg daily for 5 days (300-mg group; n = 63). Hydrocortisone was stopped abruptly at the end of treatment. Results: There were no significant differences between the 200-mg and 300-mg groups as concerns 28-day mortality (respectively 52.5% vs. 44.4% [RR 0.84, 95% CI, 0.58–1.22, P = 0.47]), refractory shock incidence or delay from shock to vasopressor cessation. There were also no differences in adverse events between the groups. Shock relapse after hydrocortisone cessation was independent of hydrocortisone regimens, but it was associated with the persistence of infection and the use of etomidate. The resumption of hydrocortisone due to shock relapse was significantly more frequent in the 300-mg group. Conclusion: We found no differences in mortality or adverse events between the two hydrocortisone administration regimens. Shock relapse was significantly associated with the persistence of infection and the use of etomidate.